Technology Entrepreneurship Project (ENT 600) : Logitech International S.A. / Muhammad Azam Muhammad Kamal - Muhammad Kamal, Muhammad Azam (2022)
This case study is about Logitech International S.A. which is one of the world's leading manufacturers of input and interface devices for personal computers (PCs) and other digital products. The products that have been produce by this company are known worldwide because of the reputations and the brand name. From this study, we can learn to analyse, apply the knowledge, reasoning and drawing conclusions to understand this company even more. The first part of this case study has been focusing on collecting the company information such as the background of the company, the problem statement, and the purpose of the study. Through the analysis, there are some problems that could be identified in the company. These problems were studied, and some solutions and improvement were proposed to achieve a better-quality product that being known by customers from all around the globe. The second part of the case study focuses on its’ background, organizational structure, products and services, technology, business, marketing, and operational strategy. For the third part, we only use SWOT, which is the short form for strength, weaknesses, opportunities, and threats of this company in order to analyse the product or services of the company and to understand more on how the company works. The fourth part is for me to find the findings and discussion for this report of case study about Logitech International S.A. and for the last one is for the recommendation and improvement section.